The use of information by teachers of the secondary level in Mexico - Guevara Villanueva, Angélica (Revista General de Información y Documentación, 2015)
The following research shows the results obtained through interviews to the members of a teachers’ community in the secondary school level. These teachers are in charge of groups of students in Mexico City in schools of general type. The purpose of the research was the analysis of the habits in the research of information needed for their teaching and to comply with the official policies in education assessment. In this respect, we give a general mention about previous studies of this kind in scientific and academic communities, as well as in teachers’ communities in schools of specific types in Mexico. We also describe the methodological elements which conducted the research process for a interviews the teachers. Finally we make a results and give the conclusions.